Outdoing the Joneses: Understanding community acceptance of an alternative water supply scheme and sustainable urban design - Dzidic, Peta; Green, M. (Elsevier B.V, 2012)
Concern regarding the sustainability of Australia's potable water supply has prompted investigation into the use of alternative water supply options and other sustainable urban design features at the household and neighbourhood level. This paper details a mixed methodology research project exploring the acceptability of a non-potable groundwater supply system, as well as attitudes towards and uptake of other sustainable urban design options. Results from a photo-elicitation survey depicting aesthetically degraded water in different use scenarios demonstrate that overall participants are accepting of some degree of aesthetic degradation for all uses; however issues relating to fairness and ‘keeping up appearances’ were raised. When asked about sustainable urban design options most participants felt these were important to have, yet few had these in their homes, and noted many barriers to adoption. Notable during interviews was the reported pressure to out-do others in the neighbourhood with respect to home upkeep. Findings from our research suggest that normative processes are highly important, seen to shape the way in which people engage with sustainable urban design in the public/private space, as well as the expectations that they have on others and themselves. We suggest that current social norms need to be challenged to encourage home owners to adopt more sustainable practices or utilised so that new developments present an opportunity for neighbours to compete over the ‘greenest’ housing design rather than the greenest lawn.